CONVERSION EFFICENCY OF THE YAG:CE LUMINOPHORES COOPERATED WITH UV-VIS SEMICONDUTOR EMMITERS - Prorok, Mateusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Commonly used white light emmision method utilizing LED technology depends mostly on luminophore and wavelenght 440–460 nm (blue) semicondutor emiter use. Emission of the wide visible spectrum, greenish yellow in colour, is an effect of fotoluminescence in cerium doped YAG cristal based luminophore. As the effect of fotoluminescence, radiation interferes with source radiation, resulting in white colour light with colour temperature depending on luminophore type. The article presents the research on both conversion efficency of the luminophore and the spectra response for the non-dedicated forcing, realised by usage of semiconductor emitters.